HIGH PERCENTAGE OF RARE EARTH ELEMENT CONNECTION WITH THE ACCUMULATION SEDIMENT AS RESPONSE LONGSHORE CURRENTS IN THE BELITUNG WATERS - Delyuzar Ilahude; Maman Surachman (BULLETIN OF THE MARINE GEOLOGY, 2015)
The study area is geographically located in the West coast of Belitung island at coordinates 105o48'00" - 106o06' 00" E and 06o46'00" - 06o50' 00" S. The beach and coastal area is influenced by wave energy from the West and North directions The purpose of this study is to analyze the relationship between the zone of sediment accumulation of empirical approaches on oceanography parameter containing rare earth elements. The approach used is to predict the shore wave energy using wave prediction curve deep waters to obtain the energy flux of the wave at each point of reference. Sediments containing rare earth elements tend to lead to the south as a result of the movement of longshore currents. Regional coastal area of the western part of the island of Belitung, especially in the southern part of the estuary of the river Tanjung Pandan is estimated to be a zone of sediment accumulation. The movement of sediment caused by wave energy from the north led to sedimentation evolved significantly in the south which is thought to contain rare earths minerals derived from land. This sedimentation process takes place on a seasonal basis, which allegedly took place in the west. The movement of sediment to the south of the mouth of the Cerucuk River it is predicted that rare earth elements were supplied from these rivers tend to settle in the southern part of the estuary Cerucuk throughout the year.Keywords: accumulation of sediment, longshore currents, rare earth elements offshore Belitung Lokasi daerah penelitian secara geografis terletak di pesisir pantai barat Pulau Belitung pada koordinat 105o48'00" - 106o06'00" BT dan 06o46'00" - 06o50'00"LS. Pesisir pantai termasuk pantai terbuka terhadap pengaruh energi gelombang dari arah barat dan utara. Tujuan dari penelitian ini untuk melakukan analisis hubungan antara zona akumulasi sedimen dari pendekatan empirik parameter osenografi dan kandungan unsur tanah jarang. Pendekatan yang digunakan yaitu dengan memprediksi energi gelombang pantai menggunakan kurva prediksi gelombang perairan dalam untuk memperoleh energi fluks gelombang pada setiap titik referensi. Pengendapan sedimen bermuatan unsur tanah jarang cenderung mengarah ke selatan sebagai akibat dari pergerakan arus sejajar pantai. Daerah kawasan pesisir bagian barat Pulau Belitung terutama di bagian selatan muara sungai Tanjung Pandan diperkirakan menjadi zona akumulasi sedimen. Pergerakan sedimen akibat dari energi gelombang dari arah utara menyebabkan adanya sedimentasi berkembang cukup signifikan di bagian selatan yang diduga bermuatan mineral unsur tanah jarang asal dari darat. Proses sedimentasi ini berlangsung secara musiman, yang kemungkinan berlangsung pada musim barat. Adanya pergerakan sedimen ke arah selatan dari muara Sungai Cerucuk maka diperkirakan unsur tanah jarang yang dipasok dari sungai tersebut cenderung mengendap di bagian selatan dari muara Sungai Cerucuk sepanjang tahun. Kata kunci: akumulasi sedimen, arus sejajar pantai, unsur tanah jarang lepas pantai Belitung